Emotional profile of athletes before competition: contributions for perceived stress, cognitive appraisal and coping strategies - Nogueira, José Miguel; Morais, Catarina; Mansell, Paul; Gomes, A. Rui (Frontiers in Sports and Active Living, 2025)
IntroductionUnderstanding athletes' emotional experience prior to competition is crucial for examining their adaptation to stress. Earlier research suggested anxiety impaired performance by disrupting tasks like information processing, attention, and concentration—leading to increased stress and perceived threat. Over time, focus shifted toward understanding how athletes' interpretations of anxiety could influence performance positively. This led to broader research into other emotions typically considered “negative” (e.g., anger, dejection) and “positive” (e.g., excitement, happiness). However, how these emotions influence performance and interact with intensity has been under-studied.MethodsA total of 383 elite athletes completed a questionnaire 24–48 h before a major competition, assessing overall stress, emotional intensity (excitement, happiness, anxiety, anger, dejection), emotional direction, cognitive appraisal, and coping strategies.ResultsA cluster analysis based on emotion intensity and direction identified three athlete profiles: “Emotionally Balanced” (moderate intensity), “Facilitating Arousal Profile” (mixed intensity, all emotions viewed as performance-enhancing), and “Low Arousal Profile” (low emotional intensity). Despite differing emotional profiles, athletes reported similar stress levels before competition. However, those in the “Facilitating Arousal Profile” reported greater challenge appraisals, perceived control, and use of adaptive coping strategies compared to others.DiscussionThese findings suggest that not just emotional intensity but also the perceived impact of emotions plays a key role in performance. These results have important implications for psychological interventions, emphasizing the need to consider both how emotions are experienced and how they are interpreted in the context of competition.